PETA PUZZLE 3D BERBASIS MOBILE AUGMENTED REALITY SEBAGAI PROTOTIPE MEDIA PEMBELAJARAN GEOGRAFI - Rakhmat Jaya Lahay; Nurdin Mohamad (Universitas Negeri Gorontalo, 2020)
Presentation of maps in paper form is still often done. The advancement of mobile devices and the support of augmented reality technology are alternatives in making map media presentations more interesting and interactive. This research aims to develop media prototypes in the form of educational games based on mobile augmented reality. Media development is carried out using a prototype approach. The developed media is able to display 3D map objects properly based on the results of black box testing and beta testing. Black box testing shows that the media functions as needed. Beta testing states that this application can be accepted with the percentage of survey results is 89.7%.